Analisis Spasial Tingkat Kerawanan Jalur Pipa Panasbumi Di Area Kamojang, Kabupaten Bandung, Jawa Barat Tahun 2016 - Arianto, Ivan; , Dr. Ir. Imam Hardjono, M.Si (2016)
Spatial analysis of the level of insecurity geothermal pipeline is a method to determine and produce results in anticipation of and prevent the occurrence of material losses and the soul in the event of problems in geothermal pipeline. This analysis can be used to assess the level of insecurity geothermal pipeline that passes means and public facilities so as not to endanger the impact on the surrounding community. This analysis aims to (1) Analyze potential in case of leaks and explosions that occur from geothermal pipeline by using a geographic information system (GIS); (2) examine the preparedness and readiness in the process of overcoming the problems caused by leakage and damage to the pipeline geothermal; (3) the Use of spatial analysis so that it can help reduce the risk of loss in case of damage and leakage of the heat pipe. Methods undertaken in carrying out the analysis using the method of field survey and analysis of spatial form Buffering using GIS software.The results of research that is in the form of a spatial analysis of the level of risk of the insecurity of geothermal pipeline which passes through the settlements and public facilities so that they can anticipate and perform emergency response in the event of unexpected problems on geothermal pipeline.